Brexit: What are the lessons? - Vibert, Frank (Revista Mexicana de Sociología, 2020)
In June 2016 the electorate in the United Kingdom voted in favour of leaving the eu where the UK had been a member since 1973.Turnout was high (over 70%) but the margin was small (52% for leave and 48% for remain).